Green open space mapping and carbon stock estimation in Surakarta - Suhardono Sapta; Wahyuni Titi; Abu Nazar Irfan; Maulida Ibriza Naila; Wijayanti Sovia (E3S Web of Conferences)
Development and urbanization have had a significant impact on the layout and land use in Surakarta. The research aims to map how far green open spaces have changed and estimate carbon reserves in Surakarta in 2019-2023. Green open space was mapped by accessing Sentinel 2A obtain by Google Earth Engine, whereas carbon stocks were assessed in each density class by the formula between carbon storage and NDVI values per pixel. The results, based on five years of annual data, indicate regions (GOS) with an extremely high concentration of vegetation decreased from 5,880 hectares in 2019 to 4,899.2 hectares in 2023. This trend reflects a loss in places with dense vegetation. Vegetation as the most substantial contributors to carbon stocks, based on data indicate the cumulative carbon storage decreased from 12,933,424.55 kg in 2019 to 12,518,281.65 kg in 2023, resulting in a loss of around 415,142.9 kg of carbon at the site during the past five years. These findings contribute to a greater understanding of plant dynamics and carbon storage capability in urban environments that giving useful insights for environmental planning and management in large cities.